2017
DOI: 10.1039/c7nr05859d
|View full text |Cite
|
Sign up to set email alerts
|

Carbosilane dendrons with fatty acids at the core as a new potential microbicide against HSV-2/HIV-1 co-infection

Abstract: Herpes simplex virus type 2 (HSV-2) and human immunodeficiency virus type 1 (HIV-1) represent the two most frequent sexually transmitted infections (STI) worldwide. Epidemiological studies suggest that HSV-2 increases the risk of HIV-1 acquisition approximately 3-fold mainly due to the clinical and immunological manifestations. In the absence of vaccines against both STI, the development of new preventive strategies has become essential for further studies. We performed the screening of six novel polyanionic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…(Petrova et al, 2013). It is also essential to evaluate API's ability to inhibit other STIs, such as HIV‐2, HSV‐2, HPV, hepatitis viruses, and other pathogens associated with vaginosis or candidiasis (chlamydia, gonorrhea, or syphilis; Briz et al, 2015; Cena‐Diez, Vacas‐Cordoba, et al, 2016; Guerrero‐Beltran et al, 2017; Sepulveda‐Crespo, Jimenez, et al, 2017; Telwatte et al, 2011).…”
Section: In Vitro Preclinical Studiesmentioning
confidence: 99%
“…(Petrova et al, 2013). It is also essential to evaluate API's ability to inhibit other STIs, such as HIV‐2, HSV‐2, HPV, hepatitis viruses, and other pathogens associated with vaginosis or candidiasis (chlamydia, gonorrhea, or syphilis; Briz et al, 2015; Cena‐Diez, Vacas‐Cordoba, et al, 2016; Guerrero‐Beltran et al, 2017; Sepulveda‐Crespo, Jimenez, et al, 2017; Telwatte et al, 2011).…”
Section: In Vitro Preclinical Studiesmentioning
confidence: 99%
“…Besides their own antiviral activity, Muñoz-Fernández et al showed that their combination with Tenofovir and Maraviroc (two antiviral agents) produce almost complete inhibition of HIV infection and transmission [ 80 ]. Carbosilane dendrimers are also efficient towards HIV-HSV coinfection [ 81 ] and can be employed in the development of fast diagnostic assays based on dendronized magnetic nanoparticles [ 82 ] tools. Dendrimers can also contribute to the design of efficient vaccines against HIV, such as the PEG-citrate G2 dendrimer bearing multiple HIV epitopes which produced a significant cellular immune response in vivo and a higher Th1 response compared to Th2 [ 83 ].…”
Section: Dendrimers and Dendritic Materials In The Prevention Trementioning
confidence: 99%
“…No mortality or sign of vaginal discharge, erythema, edema, irritation, or inflammation at the lowest dose (5 mM) or a higher dose (50 mM) of G2-S16 PCD were detected. No characteristic abnormalities were found during the histopathological analysis of vaginal tissues, compared to the negative control [53,67,99,114]. Moreover, G2-S16 PCD was intravaginally applied for 7 consecutive days in BALB/c mice, at different doses and concentrations, based on the available literature [115], and pathological examinations of vaginal tissues were performed.…”
Section: Biocompatibilitymentioning
confidence: 99%